Cosmetic outcome assessement after two methods of breast conserving surgery in patients with early advanced breast cancer - Zadrożny, Marek (Menopause Review/Przegląd Menopauzalny, 2003)
Objective: The aim of this study was to evaluate the early and long-term cosmetic outcome after conserving surgery of the early breast cancer. Material and methods: In the period 1.01.1999–31.03.2002 in our Institute 131 patients were operated on by the authors. 77 of them underwent quadrantectomy and 61 – local wide excision. An early and long-term cosmetic outcome was assessed both by patients and the surgery team, using the modified Al-Ghazal scale. Results: Excellent and good long-term results have been achieved in 80% of cases as assessed by the surgery team and in 77% in the opinion of the patients. In 83% of cases a satisfactory result was achieved with a tumor localized in the upper outer quadrant of the mammary gland. Conclusions: Comparing both surgical procedures, quadrantectomy has been found to be a good alternative to local wide excision only in the case of upper outer quadrant localization of the tumor. A definitively negative impact of postoperative radiotherapy on the long-term cosmetic result has been clearly shown.